Lansoprazole promotes cisplatin‐induced acute kidney injury via enhancing tubular necroptosis. Issue 5 (18th February 2021) - Ye, Lin; Pang, Wanxia; Huang, Yanheng; Wu, Hongluan; Huang, Xiaorong; Liu, Jianxing; Wang, Shujun; Yang, Chen; Pan, Qingjun; Liu, Huafeng
Abstract: Acute kidney injury (AKI) is the main obstacle that limits the use of cisplatin in cancer treatment. Proton pump inhibitors (PPIs), the most commonly used class of medications for gastrointestinal complications in cancer patients, have been reported to cause adverse renal events. However, the effect of PPIs on cisplatin‐induced AKI remains unclear. Herein, the effect and mechanism of lansoprazole (LPZ), one of the most frequently prescribed PPIs, on cisplatin‐induced AKI were investigated in vivo and in vitro. C57BL/6 mice received a single intraperitoneal (i.p.) injection of cisplatin (18 mg/kg) to induce AKI, and LPZ (12.5 or 25 mg/kg) was administered 2 hours prior to cisplatin administration and then once daily for another 2 days via i.p. injection. The results showed that LPZ significantly aggravated the tubular damage and further increased the elevated levels of serum creatinine and blood urea nitrogen induced by cisplatin. However, LPZ did not enhance cisplatin‐induced tubular apoptosis, as evidenced by a lack of significant change in mRNA and protein expression of Bax/Bcl‐2 ratio and TUNEL staining. Notably, LPZ increased the number of necrotic renal tubular cells compared to that by cisplatin treatment alone, which was further confirmed by the elevated necroptosis‐associated protein expression of RIPK1, p‐RIPK3 and p‐MLKL. Furthermore, LPZ deteriorated cisplatin‐induced inflammation, as revealed by the increased mRNA expression of pro‐inflammatory factors including, NLRP3, IL‐1β, TNF‐α and caspase 1, as well as neutrophil infiltration. Consistently, in in vitro study, LPZ increased HK‐2 cell death and enhanced inflammation, compared with cisplatin treatment alone. Collectively, our results demonstrate that LPZ aggravates cisplatin‐induced AKI, and necroptosis may be involved in the exacerbation of kidney damage.